PERAN KEPALA DESA RANAH SUNGKAI KECAMATAN XIII KOTO KAMPAR KABUPATEN KAMPAR DALAM PEMBANGUNAN INFRASTRUKTUR JALAN TAHUN ANGGARAN 2023-2024 - Putri, Sofia Riani; Amin, Raja Muhammad (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2026)
This research is motivated by the condition of road infrastructure in Ranah Sungkai Village, which has suffered severe damage, including a 7 km ring road, a 600 m educational road, and a 12 m inter-hamlet bridge. Such conditions hinder community mobility, agricultural distribution, access to education, and health services. This study aims to analyze the role of the village head as a motivator, facilitator, and mobilizer in road infrastructure development for the 2023-2024 fiscal year. The research method employed is descriptive qualitative with data collection techniques through in-depth interviews, field observations, and documentation. The findings reveal that the village head has made efforts to motivate the community, facilitate planning, and mobilize residents through collective work (gotong royong). However, the effectiveness of the village head’s role remains low due to limited community participation, weak budget supervision, and insufficient development funds. Overall, the role of the village head is crucial in determining the success of road development, yet greater innovation, transparency, and collaboration among the village government, local residents, and the district government are required to ensure more effective and sustainable infrastructure development. Keywords: Village Head Role, Motivator, Facilitator, Mobilizer, Road Infrastructure